Employability Competences of Future Primary Education Teachers: A look at their Social and Labor Insertion Process - González Lorente, Cristina (2018)
In the learning society, one of the challenges for teachers in training is the need to define and develop a set of professional skills in their initial training, essential for their subsequent entry into the labor market. In this work, the aim was to delve into the employability skills developed by students in the Primary Education undergraduate study program, their relevance for their process of socio-labor insertion, as well as their global perception to face it. An inter-university study was carried out with a total of 210 students in their final year at Universidad de Murcia and Universidade da Coruña, both Spanish. The collection of information was carried out on the basis of the previously validated Labor Counseling and Insertion Questionnaire. The results showed few differences between the assessments of the students of both universities, which coincide in pointing out to a greater relevance of the competences as opposed to the level of development in the classroom. In short, attention should be directed to joining efforts by the Spanish government in the initial training of primary education teachers, so that they can acquire a set of competences that will allow a continuous improvement and updating in their professional, social and personal performance, in addition to their career inception